‘Urf Tebbasan Jagung Masyarakat Sembilangan Kecamatan Bangkalan : (Menakar Praktik Tradisi Dalam Perspektif Hukum Islam) - Khoirun Nasik (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2020)
Corn cutting has become a rooted tradition in the Sembilangan community. A village is located in Bangkalan Madura District. Unlike the general muamalah transaction rules which require that the goods be certain and clear. This practice uses a sampling technique to determine the quality of the maize. Each paddy field is taken five to seven fruits. Meanwhile, determining the price based on land area. This research is a type of field research with a descriptive analysis method with a juridical empirical approach. The primary data source used is data obtained from the local village, while the secondary data source is obtained from books related to buying and selling, one of which is the fiqih mu'amalah book. The results showed that the sale and purchase of maize by means of slaughter included 'urf which is not against syar'i, entered into the jizaf (estimation) buying and selling model, namely buying and selling without knowing the content of the goods and the scales in detail, but basically the goods those that are sold have certain measurements, weights or numbers in detail. Buying and selling jizaf is a light gharar category.